Low Literacy And Public Participation In Sharia Financial Institutions: A Qualitative Study In Jambesari Darussholah Village - Delalatul Islami; Haqiqotus Sa’adah (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
Jambesari Village is classified as a village with a relatively low level of literacy and community participation. Although some members of the community are aware of the existence of Islamic financial institutions, many do not yet have an in-depth understanding of these institutions, including their basic principles and operational systems. This study aims to analyze the level of Islamic financial literacy, the factors contributing to low community participation, and strategies to enhance both literacy and participation. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. Data analysis is conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of this study indicate that the low level of community literacy and participation in Islamic financial institutions is caused by a lack of socialization and limited access to Islamic financial institutions in the village. Therefore, strategies or efforts are needed to improve community literacy and participation, which can be implemented through long-term socialization programs and the expansion of access to Islamic financial services in the village, so that the level of community literacy and participation can increase.